A revision of pipistrelle-like bats (Mammalia: Chiroptera: Vespertilionidae) in East Africa with the description of new genera and species. Issue 4 (10th September 2020) - Monadjem, Ara; Demos, Terrence C; Dalton, Desire L; Webala, Paul W; Musila, Simon; Kerbis Peterhans, Julian C; Patterson, Bruce D
Abstract: Vespertilionidae (class Mammalia) constitutes the largest family of bats, with 500 described species. Nonetheless, the systematic relationships within this family are poorly known, especially among the pipistrelle-like bats of the tribes Vespertilionini and Pipistrellini. Perhaps as a result of their drab pelage and lack of obvious morphological characters, the genus and species limits of pipistrelle-like bats remain poorly resolved, particularly in Africa, where more than one-fifth of all vesper bat species occur. Further exacerbating the problem is the accelerating description of new species within these groups. In this study, we attempt to resolve the systematic relationships among the pipistrelle-like bats of sub-Saharan Africa and Madagascar and provide a more stable framework for future systematic efforts. Our systematic inferences are based on extensive genetic and morphological sampling of > 400 individuals covering all named genera and the majority of described African pipistrelle-like bat species, focusing on previously unstudied samples of East African bats. Our study corroborates previous work by identifying three African genera in Pipistrellini ( Pipistrellus, Scotoecus and Vansonia ), none of which is endemic to Africa. However, the situation is more complex in Vespertilionini. With broad taxonomic sampling, we confirm that the genus Neoromicia is paraphyletic, a situation that we resolve by assigning the species of Neoromicia to four genera. Neoromicia is here restricted to Neoromicia zuluensis and allied taxa. Some erstwhile Neoromicia species are transferred into an expanded Laephotis, which now includes both long-eared and short-eared forms. We also erect two new genera, one comprising a group of mostly forest-associated species (many of which have white wings) and the other for the genetically and morphologically unique banana bat. All four of these genera, as recognized here, are genetically distinct, have distinctive bacular morphologies and can be grouped by cranial morphometrics. We also demonstrate that the genus Nycticeinops, until now considered monospecific, includes both Afropipistrellus and the recently named Parahypsugo, thus representing the fifth African genus in Vespertilionini. A sixth genus, Hypsugo, is mostly extra-limital to sub-Saharan Africa. Finally, we describe three new species of pipistrelle-like bats from Kenya and Uganda, uncovered during the course of systematic bat surveys in the region. Such surveys are greatly needed across tropical Africa to uncover further bat diversity.